Hubungan Lokus Kendali Internal dan Dukungan Sosial Dengan Kesejahteraan Psikologis pada Penyandang Disabilitas di Aceh Tengah - Rahmania Rahmania; Abdul Munir; Zuhdi Budiman (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
This study aims to determine the relationship of internal locus of control and social support with psychological wellbeing Disability in Aceh Tengah.The research using correlational quantitative methods. The sample of this study amounted to 93 students with disability by using simple random sampling technique. Data collection methods in this study using three scales, namely the scale of Psychological Wellbeing, Scale Locus Of Internal Control and Social Support Scale. Data analysis is Multiple Regression. The results of this study show (1) There is a significant positive relationship between internal locus of control and social support with psychological well-being, with coefficient rx12y = 0,592 with p = 0,000 with contribution of 35%. (2) there is a significant positive relation between locus of control Internal with psychological well-being, with coefficient rx1y = 0.337 with p = 0,000 with contribution of 11.3%. (3) there is a significant positive correlation between social support and psychological well-being, with coefficient rx2y = 0,554 with p = 0,000 with contribution of 30,7%, hence can be concluded that hypothesis accepted.